When Students Design University: a Case Study of Creative Interdisciplinarity between Design Thinking and Humanities - Molinari Alessandra; Gasparini Andrea Alessandro (De Gruyter, 2019)
This paper addresses the issue of how to enhance student participation in university governance. This issue is approached by taking into account the growing pressures of the European Commission's modernization agenda on the educational policies of the European Higher Education Area, and by focusing on the way these pressures affect students' conceptions of themselves and of the mission of higher education. The thesis presented in this paper is that design thinking and the humanities share a common epistemological core that enables them, if applied in educational settings, to play a major role in fostering students' trust in their governance skills and in their ability to influence educational policies through a creative mindset and a deeper comprehension of the stakes in present-day higher education. An experimental workshop combining design thinking with the humanities and with the constructivist approach of student-centered learning was held within a course in a humanities bachelor program on the basis of a heuristic framework developed through an interdisciplinary research process. This process was conducted according to the principles of design and hermeneutics. The outcomes of the workshop in terms of the participants' enhanced self-confidence and decisional skills validate the thesis of this study.